Impact of physical education and recreational activities with elements of roller skating on the morphofunctional state of schoolchildren in grades 5-6 - Nataliia Pangelova; Sofiia Vlasova (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to determine the impact of fitness classes with the priority use of roller skating on the morphofunctional state and physical fitness of schoolchildren in grades 5-6. Material & Methods: 194 children of 10-12 years old took part in the experiment, 90 of them were boys and 104 girls. The study was conducted on the basis of school number 269, Kiev with in-depth study of the French language. In the process of research, the following methods were applied: pedagogical (pedagogical experiment and observation); anthropometric; physiological (pulsometry, spirometry, functional tests) methods of mathematical statistics. Results: study shows that among pupils in grades 5-6, physical culture and fitness classes with priority use of roller skating means cause positive changes in the morphofunctional state and physical fitness. Significant improvements were found after 9 months of regular classes. Conclusion: fitness classes with the priority use of roller skating means have a positive effect on the morphofunctional state and physical fitness of students in grades 5-6. It was revealed that the indicators of the functional state (in particular, the cardiovascular and respiratory systems), physical fitness of students compared with the initial data are significantly higher (P(t)<0,01; P(t)<0,001).